Stakeholder Engagement and Environmental Practice Adoption: The Mediating Role of Process Management Practices. (30th September 2016) - Jakhar, Suresh Kumar
Abstract: This study extends the current research on diverse organizational responses to stakeholder demands on environmental practice adoption. I argue that process management practices influence 'green' innovation and that these differences in their adoption level engender heterogeneous responses to similar stakeholder pressures. Theoretically, the proposed relationship is supported by the relationship between institutional theory, the resource‐based view of the firm and complementary assets. The proposed relationship is empirically tested using original survey data obtained from Indian manufacturing facilities. Results obtained using the structural equation modeling approach support the proposed hypothesis that process management practices mediate the relationship between stakeholder pressure and environmental practice adoption. This study contributes to a theoretical and practical understanding of why there is an idiosyncratic organizational response to environmental demand, by analyzing institutional factors (stakeholder pressure) as predictors and internal firm resources and capabilities as mediators. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment